Cationic metal–organic framework porous membranes with high hydroxide conductivity and alkaline resistance for fuel cells. Issue 38 (15th September 2016) - Wu, Bin; Ge, Liang; Yu, Dongbo; Hou, Linxiao; Li, Qiuhua; Yang, Zhengjin; Xu, Tongwen
Abstract : A sandwiched AEM was prepared from porous BPPO entrapped cationic MOFs with a PVA coating on the two sides and demonstrated high hydroxide conductivity and alkaline stability. Abstract : Hydroxide conductivity and alkaline stability are challenging issues for anion exchange membrane fuel cells (AEMFCs). Here, a novel sandwiched anion exchange membrane (AEM) was prepared from porous bromomethylated poly(2, 6-dimethyl-1, 4-phenylene oxide) (BPPO) entrapped cationic metal–organic frameworks (MOFs) with a polyvinyl alcohol (PVA) coating on the two sides. The porous BPPO matrix prepared by a non-solvent induced phase separation (NIPS) method provides numerous interconnected nanopores and sponge-like walls and enhanced uptake of alkali. The entrapped cationic MOFs can work as OH − conductive channels while the PVA coating can block the crossover of fuels such as methanol. The final membranes can reach an OH − conductivity of 145 mS cm −1 at 80 °C and a methanol permeability of 3.68 × 10 −7 cm 2 s −1, the performance of which is much higher than that in the existing literature.